Penguatan Pendidikan Keluarga terhadap Karakter Anak Milenial di Era Modernisasi dalam Perspektif Surah Luqman Ayat 12-19 dan Hadis Tentang Pemimpin - Maulida, Ghina Rahmah; Musthofa, Tulus; Saidah, Nur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The era of modernization is an era of change from traditional to advanced (modern), such as current conditions which cover various aspects, including education. In the modernization period, education focuses on developing students' character. This approach aims to form a good personality that is able to adapt to current developments, which is greatly influenced by the role of the teacher. This research aims to identify and describe the contribution of teachers in shaping student character in the era of modernization. The literature study method is used to collect data from various sources, such as journals and articles. Data analysis techniques involve reading and discussion to formulate information comprehensively. Research findings show that Islamic character education based on local wisdom is strengthened by the role of parents in teaching manners. The four foundations of character education include religious values, culture, environment and individual potential, with religious values as the main foundation. The moral message from Luqman Al-Hakim in Q.S. Luqman verses 12-19 highlight the urgency of guiding children's faith with monotheism from an early age, teaching them to be grateful to Allah and filial piety to their parents, educating children to do good deeds, teaching them to act virtuously and avoiding evil, and preparing children with noble morals and good manners in interacting. This message reflects the central role of Islamic education in shaping an individual's personality and morals, with a focus on the principles of monotheism and ubudiyah behavior. Keywords: Family Education; Millennial Character; Modernization Era.